Coding continental: information design in sixteenth‐century English vernacular language manuals and translations. Issue 1 (February 2015) - Armstrong, Guyda
<x xml:space="preserve">Abstract</x> This article explores the late‐sixteenth‐century Italian‐English translated book via an investigation of its visual, textual, and paratextual expression on the page. Drawing on approaches from textual and material history, bibliography, and translation studies, I unpack the constituent elements of the page to draw new conclusions about the functions of the forms of these specific book‐objects. Using a selection of texts of Italian origin, printed in London in a variety of publishing genres in the latter part of the sixteenth century (mostly, but not exclusively the 1580s and 1590s), I approach these books as much in terms of their visual design as their Italian content. Target editions discussed include three translations from Boccaccio, landmark print productions of other authors such as Ariosto, Castiglione, and Tasso, as well as parallel‐text bilingual or polyglot language‐learning books. How far do the visual codes and organization of the book‐object create its status as a translation, and can these be differentiated from those of the non‐translated book? In answering this question, I 'translate' key terminology from the discipline of translation studies more usually applied to linguistic transfer (such as 'equivalence', 'domestication'; 'foreignization'), and newer approaches such as multi‐modal theory, to the information design of the early modern page.